Rancang Bangun Sistem Informasi Persatuan Orang Tua Murid dan Guru - Mulyani, Asri; Nashrulloh, Muhammad Rikza; Nurmahmudi, Raihan (Jurnal Algoritma, 2025)
TK Persis Tarogong is one of the growing and developing educational institutions in the Garut district, especially in terms of technological development and school information. The author intends to contribute to the educational institution of TK Persis Tarogong by planning a web-based Parent Student and Teacher Association Information System, which aims to support the smooth learning process as well as assist parents in monitoring their children and obtaining information on POMG activities. This information system uses the RUP (Rational Unified Process) development method with the stages of Inception, Elabolation, Construction, and Transition. The system design used in this research is web-based using UML, the UML design built is Usecase Diagram, Squence Diagram, Activity Diagram and Class Diagram. The result of this research is a web-based information system that is expected to help parents and teachers at Persis Tarogong Kindergarten. The contribution of this research is that it can help TK Persis Tarogong in developing technology and school information.